Not a Temple but a Tomb: The Architectural Drawings on Pap. Berlin P 15781 and 15782A + B - Dorn, Andreas (Zeitschrift für ägyptische Sprache und Altertumskunde, 2024)
Based on a reassessment of the papyri Pap. Berlin P 15871 and 1582A+B with the correction of several readings, particularly one of the three determinatives of (i) “shrine”, the key word for their earlier interpretations, it is suggested that the architectural drawings do not show a rock cut temple or a hemi-speos but KV 5, the so-called tomb of the sons of Ramesses II in the Valley of the Kings. Differences in the handwriting, in the depiction of the bedrock pattern surrounding the rectangular rooms, and other observations suggest that more than one person was involved in the creation of the architectural drawings. As suggested in the past, they belonged to at least two different papyri. Terms referring to work in progress indicate that the papyri are related to work in progress, as opposed to other architectural drawings which represent the beginning or final stages of tomb construction projects.